2016
DOI: 10.1186/s12864-016-2476-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of weighted co-regulatory networks in maize provides insights into new genes and regulatory mechanisms related to inositol phosphate metabolism

Abstract: BackgroundD-myo-inositol phosphates (IPs) are a series of phosphate esters. Myo-inositol hexakisphosphate (phytic acid, IP6) is the most abundant IP and has negative effects on animal and human nutrition. IPs play important roles in plant development, stress responses, and signal transduction. However, the metabolic pathways and possible regulatory mechanisms of IPs in maize are unclear. In this study, the B73 (high in phytic acid) and Qi319 (low in phytic acid) lines were selected for RNA-Seq analysis from 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 97 publications
2
22
0
Order By: Relevance
“…The differential expression of transcription factor genes such as WRKY and CAMTA (Calmodulin-binding Transcription Activator), was linked to phytic acid biosynthesis pathway, suggesting a complex regulatory mechanism (Redekar et al, 2015 ). Association of WRKY transcription factors and Ca 2+ binding activity with inositol metabolism was also confirmed by another independent study with maize low phytic acid breeding line Qi319 (Zhang et al, 2016 ). Zhang et al ( 2016 ) also identified ABC transporter gene candidates associated with low phytic acid phenotype in maize using co-regulatory network.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…The differential expression of transcription factor genes such as WRKY and CAMTA (Calmodulin-binding Transcription Activator), was linked to phytic acid biosynthesis pathway, suggesting a complex regulatory mechanism (Redekar et al, 2015 ). Association of WRKY transcription factors and Ca 2+ binding activity with inositol metabolism was also confirmed by another independent study with maize low phytic acid breeding line Qi319 (Zhang et al, 2016 ). Zhang et al ( 2016 ) also identified ABC transporter gene candidates associated with low phytic acid phenotype in maize using co-regulatory network.…”
Section: Introductionmentioning
confidence: 53%
“…Association of WRKY transcription factors and Ca 2+ binding activity with inositol metabolism was also confirmed by another independent study with maize low phytic acid breeding line Qi319 (Zhang et al, 2016 ). Zhang et al ( 2016 ) also identified ABC transporter gene candidates associated with low phytic acid phenotype in maize using co-regulatory network. In this article, we focus on the discovery of transcription regulatory networks to further investigate the inositol metabolism in soybean.…”
Section: Introductionmentioning
confidence: 53%
“…The goal of data-driven modeling is to identify biologically meaningful signals from genome-scale data. Data-driven modeling includes identification of causal SNPs in genome-wide association analysis ( Li et al, 2010 ; Thoen et al, 2017 ), identification of DE genes ( Geng et al, 2013 ; Bechtold et al, 2016 ), proteins ( Lumba et al, 2014 ; Mostafa et al, 2016 ), metabolites ( Töpfer and Niokoloski, 2013 ; Töpfer et al, 2014 ; Zhang S. et al, 2016 ), and the reflection of those changes in gene regulatory networks ( Zaag et al, 2015 ; Landeghem et al, 2016 ). To validate modeling results, wet-bench experiments should be performed for candidate loci.…”
Section: Modeling Of Plant Abiotic Stress Responsesmentioning
confidence: 99%
“…Through integrating transcriptome and metabolite data, gene co-expression networks related to inositol phosphate in maize [ 41 ] and fruit anthocyanin content in apple [ 42 , 43 ] were constructed by WGCNA. Recently, three types of omics data including 31,447 mRNAs, 13,175 proteins and 4267 phosphoproteins were grouped individually by WGCNA into co-expression modules, and then integrated into omics networks in a developmental atlas of maize [ 29 ].…”
Section: Introductionmentioning
confidence: 99%